Aqua coordination to attenuate the luminescence properties of europium(iii)–phosphine oxide porous coordination polymers. (18th July 2017) - Katagiri, Kosuke; Matsuo, Naoya; Kawahata, Masatoshi; Masu, Hyuma; Yamaguchi, Kentaro
Abstract : Europium(iii )–phosphine oxide porous coordination polymers (Eu–PCPs) constructed from Eu(OTf)3 and tris(4-(4′-carboxylphenyl)phenyl)phosphine oxide as ligands are reported. Abstract : Europium(iii )–phosphine oxide porous coordination polymers (Eu–PCPs) constructed from Eu(OTf)3 and tris(4-(4′-carboxylphenyl)phenyl)phosphine oxide as ligands are reported. X-Ray diffraction data of Eu–PCPs are collected at 273 K with synchrotron radiation. The europium complex is shown to crystallize in the centrosymmetric orthorhombic space group Pcca . The Eu atom is surrounded by eight neighboring oxygen atoms from six ligands and a coordinated DMF molecule. Furthermore, the two Eu centers are quadruply bridged by four carboxylates. They exhibit an infinite three-dimensional structure that incorporates an open pore structure, which is thermally robust and has an N2 Brunauer–Emmett–Teller surface area of 58.5 m 2 g −1 and a micropore volume of 0.756 cm 3 g −1 . Excitation of the materials led to five sharp emission peaks arising from the 5 D0 → 7 F J transitions ( J = 0, 1, 2, 3 and 4). The absolute quantum yield of Eu–PCPs is determined as 22% at room temperature. In addition, exposure of single crystals of Eu–PCPs to H2 O vapor causes attenuation of the luminescence intensity. This process involves a single-crystal-to-single-crystal transformation. In the crystal structures of the Eu–PCPs, the ligand exchange from DMF to H2 O, which acts to quench the lanthanide luminescence, is directly observed.